Association of Depression with Age at Natural Menopause: A Cross-Sectional Analysis with NHANES Data - An S; Ren S; Ma J; Zhang Y (International Journal of Women's Health)
Shuaiqi An,1,* Shiyan Ren,1,* Jiawen Ma,1 Yizhou Zhang1,2 1School of Basic Medical Sciences, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People’s Republic of China; 2Zhejiang Famous Chinese Medicine Clinic, the Third Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yizhou Zhang, School of Basic Medical Sciences, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People’s Republic of China, Email zhangyizhou2005@126.comPurpose: To evaluate the association between depression and age of natural menopause in American women.Patients and Methods: This cross-sectional study utilized eight cycles of the National Health and Nutrition Examination Survey (NHANES) conducted from 2005 to 2023. We assessed depression using the Patient Health Questionnaire-9 (PHQ-9). We obtained ANM information from the Reproductive Health questionnaire. We screened menopausal women between the ages of 40 and 70 years, excluding those with surgical menopause. We used multivariable logistic regression models to investigate the association between depression and ANM. Additionally, we conducted subgroup analyses and interaction tests.Results: A total of 4732 women were included, and the mean age of natural menopause was 47.9 ± 6.8 years. Of these, 1123 (23.7%) were classified as early menopause, 2971 (62.8%) as normal menopause, and 638 (13.5%) as late menopause. Preliminary analysis showed a positive association between PHQ-9 score and the risk of early menopause (OR = 1.11, 95% CI = 1.06– 1.16). After full adjustment in multivariate logistic regression, it was estimated that each one-unit increase in the PHQ-9 score was associated with a 7% increased risk of early menopause (OR = 1.07, 95% CI = 1.02– 1.12). After classifying depression into three grades: no, mild, and severe, it was found that, compared with American women without depression, the risk of early menopause increased significantly. American women with major depression had an increased risk of early menopause (OR = 2.49, 95% CI = 1.10– 5.63). In College or above (OR = 1.10, 95% CI = 1.02– 1.19), PIR≤ 1 (OR = 1.10, 95% CI = 1.04– 1.16), Current smoker (OR = 1.12, 95% CI = 1.00– 1.24), the positive association between depression and early menopause was more significant.Conclusion: In this cross-sectional study, the severity of depression in American women was positively correlated with the risk of early menopause. This suggests that women should pay more attention to their mental health and actively manage depression. For women with depression, early intervention and treatment may help improve their reproductive health and delay menopause.Keywords: depression, ANM, early menopause, National Health and Nutrition Examination Survey.